Characterization and application of zeolitic imidazolate framework-8@polyvinyl alcohol nanofibers mats prepared by electrospinning. (14th February 2017) - Fan, Xiaoxiao; Yu, Linling; Li, Lianghao; Yang, Cao; Wen, Junjie; Ye, Xiaokun; Cheng, Jianhua; Hu, Yongyou
Abstract: In this study, Zeolitic imidazolate framework-8@polyvinyl alcohol (ZIF-8@PVA) nanofibers were creatively fabricated by electrospinning technique, and the nanofibers membranes were characterized by SEM, TEM, XRD, FTIR, TG, DSC, DTA, BET. Its thermal stability, mechanical property, water stability and adsorption nature were also performed. The optimized fabrication parameter of the ZIF-8@PVA was 10 wt% and the uniform diameters of the nanofibers has been obtained. In addition, the ZIF-8@PVA nanofibers displayed unique properties such as a water stable and flexible structure. The adsorption test for Congo red treatment revealed that the nanofibers had a great adsorption performance. The results indicated that the nonwoven fiber mats had a great potential as a new type of membrane adsorbents in wastewater purification. The possible mechanism of CR adsorption onto ZIF-8@PVA was researched.